Superhydrophobicity of hierarchical nanostructure of candle soot films - A. Hankhuntond (2018)
© Published under licence by IOP Publishing Ltd. Candle soot containing carbon nanoparticles can form hierarchical structure films. We prepared soot films by using glass slides blocking candle flame in the middle of the flame. The hierarchical nanostructures of the carbon nanoparticles films were confirmed by scanning electron microscopy and transmission electron microscopy. Carbon nanoparticle size was 49.2 ± 9.0 nm from SEM, which agrees to 37.9 ± 8.5 nm from TEM. The contact angles of water droplets on these films are more than 150°, indicating superhydrophobic surface. Decrease contact angles of water droplets were observed with an increase deposition time. The decrease of contact angle was saturated at about 150° when the deposition time reaches 180 s. Cassie-Baxter state was attributed to describe superhydrophobicity of carbon nanoparticles films because the hierarchical nanostructures of the surface provide a large fraction of hollows on the surface. We proposed that the contact angle dependence on deposition time was governed by the increase of the distance between nanopillars in carbon nanoparticles films.